Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
This JIFAM Volume 7 (Special Issue 1) January 2025 publishes papers related to protection of geotechnical assets infrastructure and soil improvement methods to develop the development and sustainable asset management for infrastructures. As regulated in Indonesian Scientific Journal Accreditation, a Scientific Journal can publish the Supplement and Special Edition. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the seventh volume (special issue 1).